Nectar production and pollination in peach - Nyéki, J.; Szabó, Z.; Benedek, P.; Szalay, L. (International Journal of Horticultural Science, 2000)
Observations were made at two growing sites, Siófok and Szatymaz, in the years 1998 and 1999, on 16 peach varieties. The production of nectar was measured, the foraging behaviour of bees, fruit set and the effect of exclusion of bee visits for different periods were observed systematically.Production of nectar confirmed earlier data, 9.09 mg per flower in average. There was large variation due to variety and date of observation. Bee visits were relatively abundant. At favourable weather, 1 to 30 visits/flower/day occurred in the average. Artificial hand pollination increased fruit set, substantially. Open pollination yielded superior fruit set than self pollination, without bees. Supplementary bee pollination can be regarded to be beneficial to peach production as well.